Strategi Meningkatkan Kinerja Jaringan Komputer Berbasis Komputasi Awan - Rizki Umanti, Sri; Musyaffa Rizqie, Ibrahim; Setiawan, Muhammad Rafly (PT Jurnal Cendekia Indonesia, 2025)
The growth of cloud computing has changed how computer networks are managed in modern environments. Through cloud-based systems, organizations can utilize flexible computing resources without maintaining their own physical infrastructure. However, cloud network implementations still face performance-related challenges, including latency, bandwidth instability, and inefficient use of network resources. This study analyzes several cloud computing strategies to improve the performance of cloud-based computer networks using a literature review approach. Based on the analysis of relevant scientific publications, the findings show that strategies such as network architecture optimization, load balancing, dynamic resource management, Quality of Service (QoS) implementation, and continuous network monitoring can effectively enhance network performance. These approaches help reduce latency, improve network stability, and optimize resource utilization in cloud environments.